Laryngeal sensitivity evaluation and dysphagia: Hospital Sírio-Libanês experience - Parise Junior, Orlando; Miguel, Roberto Elias Villela; Gomes, Daniela Luci D’Aquino; Menon, Antonio Douglas; Hashiba, Kiyoshi (São Paulo Medical Journal, 2004)
CONTEXT: Laryngeal sensitivity is important in the coordination of swallowing coordination and avoidance of aspiration. OBJECTIVE: To briefly review the physiology of swallowing and report on our experience with laryngeal sensitivity evaluation among patients presenting dysphagia. TYPE OF STUDY: Prospective. SETTING: Endoscopy Department, Hospital SírioLibanês. METHODS: Clinical data, endoscopic findings from the larynx and the laryngeal sensitivity, as assessed via the Flexible Endoscopic Evaluation of Swallowing with Sensory Testing (FEESST) protocol (using the Pentax AP4000 system), were prospectively studied. The chi-squared and Student t tests were used to compare differences, which were considered significant if p < or = 0.05. RESULTS: The study included 111 patients. A direct association was observed for hyperplasia and hyperemia of the posterior commissure region in relation to globus (p = 0.01) and regurgitation (p = 0.04). Hyperemia of the posterior commissure region had a direct association with sialorrhea (p = 0.03) and an inverse association with xerostomia (p = 0.03). There was a direct association between severe laryngeal sensitivity deficit and previous radiotherapy of the head and neck (p = 0.001). DISCUSSION: These data emphasize the association between proximal gastroesophageal reflux and chronic posterior laryngitis, and suggest that decreased laryngeal sensitivity could be a side effect of radiotherapy. CONCLUSIONS: Even considering that these results are preliminary, the endoscopic findings from laryngoscopy seem to be important in the diagnosis of proximal gastroesophageal reflux. Study of laryngeal sensitivity may have the potential for improving the knowledge and clinical management of dysphagia.